Penanaman Nilai-Nilai Pendidikan Agama Islam untuk Pembentukan Karakter Siswa di SD Alam Hayuba Wlahar Wetan Kecamatan Kalibagor Banyumas - Sofa Mei Ika Sari; Muh. Hanif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to reveal: firstly an overview of character education, secondly to explain the forms of strategies used by schools in instilling character education values. The research method used in this research is a qualitative type of research, where data collection is carried out through documentation, interviews and observation. Data analysis was carried out through several stages, namely: collecting data, reducing data, presenting data and concluding. To test the validity of the data, credibility, transferability, dependability and confirmability tests were carried out. The results of the research reveal findings regarding: (1) the description and form of character education at SD Alam Hayuba Wlahar Wetan, this can be seen from the values ​​developed at the school, namely: religious values, discipline, responsibility, honesty, love of the environment, passion reading, and creative. (2) strategies used by schools and teachers in instilling educational character values, namely: role model strategy, foster care methods, enforcement of discipline, habituation activities, as well as integrity and internalization. the importance of every PAI teacher being an actor in character education in schools, manifested in systematic strategies and programs. The instilling of PAI values ​​at Alam Hayuba Elementary School contributes significantly to the formation of student character. Students show improvements in aspects of morals, discipline, responsibility and cooperation. A holistic approach and a supportive environment are key factors in the success of this program.